2020
DOI: 10.1039/c9cp06112f
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical screening of single atoms anchored on defective graphene for electrocatalytic N2 reduction reactions: a DFT study

Abstract: The reduction of molecular dinitrogen (N2) to ammonia (NH3) under mild conditions is attractive due to the wide application of ammonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…Lattice defects may cause local charge traps on the graphene surface, which has a substantial effect on improving the electronic structure and the adsorption capacity of graphene. Liu et al anchored Sc, Zn, Mo, Ru, Rh, Pd and Ag atoms on defective graphene for N 2 reduction reaction and found that a single Mo embedded on nitrogen-doped 555–777 graphene shows eminent catalytic performance [ 19 ]. Arokiyanathan et al calculated the adsorption properties of small Li clusters on graphene with Stone–Wales defect.…”
Section: Introductionmentioning
confidence: 99%
“…Lattice defects may cause local charge traps on the graphene surface, which has a substantial effect on improving the electronic structure and the adsorption capacity of graphene. Liu et al anchored Sc, Zn, Mo, Ru, Rh, Pd and Ag atoms on defective graphene for N 2 reduction reaction and found that a single Mo embedded on nitrogen-doped 555–777 graphene shows eminent catalytic performance [ 19 ]. Arokiyanathan et al calculated the adsorption properties of small Li clusters on graphene with Stone–Wales defect.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al used the DFT to screen a series of single metal atoms (Sc to Zn, Mo, Ru, Rh, Pd, and Ag)‐anchored defective graphene for the NRR. [ 85 ] First, the stability of single atom‐embedded graphene is estimated by binding the energy and equilibrium distance ( Figure a–e). It is clear that the Sc‐doped graphene holds the most stable configuration due to the most negative binding energy (about −9.5 eV).…”
Section: Graphene Derivatives and Graphene Composite Nrr Electrocatalmentioning
confidence: 99%
“…Liu et al used the DFT to screen a series of single metal atoms (Sc to Zn, Mo, Ru, Rh, Pd, and Ag)anchored defective graphene for the NRR. [85] First, the stability of single atom-embedded graphene is estimated by binding the Reproduced with permission. [66] Copyright 2018, Cell Press.…”
Section: Single Metal Atoms-and Dual Metal Atoms-anchored Graphenementioning
confidence: 99%
See 2 more Smart Citations